Water quality, metal bioaccumulation and parasite communities of Oreochromis mossambicus in Loskop Dam, Mpumalanga, South Africa - Oberholster, Paul Johan (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2012.